AMERICAN ACCOUNTING ASSOCIATION FINANCIAL REPORT For the year ended December 31, 1960. - Walgenbach, Paul H. (The Accounting Review, 1961)
This article presents financial report of American Accounting Association for the year ended December 31, 1960. The income includes member's dues, associate members' dues, subscription to the "The Accounting Review," advertising, interest, sales of membership lists and sales of other publications. Expense includes printing and mailing expense, officers, travel, meetings, and administrative expense, committee expenses, salaries and others. The article also includes Statement of Income, Life Fund for the year ended December 31, 1960.